Using Research to Ensure Quality Teaching in Rural Schools - Debra L. Holloway (Journal of Research in Rural Education, 2002)
Tbe No Child Left Rehind Act of2001. requires increased accountability for states to guarantee that all teachers ae "highhly qualified" by 2005-2006. For rural schools that often struggle t attract and retain talented teachers, ensuring teacher quality calls for careful analyses of teacher quality data and innovative policies. This paper adresses the dilemmas of increasing teacher quality in states with large proportions of rural schools. It draws upon data from recent quantitive and qualitative studies on teacher recruitment, retention, and professional learning in Wyoming, one of the most rural states in the nation. It suggests a model for examining and building a comprehensive policy that insures high quality teaching in rural schools.